High piezoelectric property with exceptional stability in self-poled ferroelectric films - Lisha Liu; Jiaojiao Yi; Kun Xu; Zhen Liu; Mingmeng Tang; Le Dai; Xuan Gao; Yang Liu; Shuhao Wang; Zhang Zhang; Liang Shu; Jing-Feng Li; et al. (Nature Communications)
Abstract Ferroelectric films are highly sought-after in micro-electro-mechanical systems, particularly with the trend towards miniaturization. However, their tendency to depolarize and degradation in piezoelectric properties when exposed to packaging procedures at temperatures exceeding 260 °C remains a significant challenge. Here, we reveal the prerequisites for self-poling and leverage these insights to achieve unprecedented macroscopic performance through a two-step approach involving texture construction and hierarchical heterogeneity engineering. The significant [001] texture and fine Zr/Ti heterogeneity, facilitated by a PbO-TiO2 buffer, enable a piezoelectric charge coefficient of 550 pC/N in self-poled Pb(Zr0.52Ti0.48)O3 film. This material demonstrates impressive resilience to elevated temperatures up to 300 °C, experiencing less than a 16% degradation in performance. Our approach can be extended to other ferroelectric systems, offering an innovative solution for high-temperature packaging and harsh environments in practical electro-mechanical applications.